Unilateral Usual Ductal Hyperplasia in A 22 Years Old Male Patient: A Case Report - Kelvin Setiawan; Bramastha Aires Rosadi; Terry Renata Lawanto; Primariadewi Rustamadji (Program Studi Ilmu Bedah, Fakultas Kedokteran Universitas Udayana, 2019)
Background: Benign breast disease have been broadly classified into non-proliferative lesions, proliferative lesions without atypia and hyperplasia with atypia. Proliferative disease, such as usual ductal hyperplasia, is associated with a 1.5 to 2 fold increased risk of developing invasive carcinoma. We reported a case of usual ductal hyperplasia in a young male. Case: A 22-year-old male complained of discomfort and enlargement of unilateral breast. Physical examination at that time revealed a palpable mass in the lateral upper quadrant of the patient’s left breast, three centimeters from nipple areola complex. The examination of axilla didn’t reveal any lymph node enlargement on both sides. His vital signs were normal without any abnormalities found on examination. Ultrasonography examination demonstrated fibroglandular tissue in the left breast with the volume of 11.13 cm3, consist of 4.8 cm length, 2.9 cm width and 0.8 cm depth. Excisional tumor biopsy was done on his left breast. Usual duct cell hyperplasia was present in microscopic examination with chronic inflammatory cells spreading around the fibrotic stromal cell. Physical examination, radiologic examination, and biopsy were all performed in this patient. Although the accuracy of the triple test is high, benign concordant results do not obviate further surveillance of a palpable mass. We advised our patient to routinely follow-up his condition every 6 months for 1 to 2 years, especially if there any changes found on his breasts. Conclusion: Any guidelines and further studies regarding patient’s follow-up examination after biopsy for male breasts tumor are needed in order of better understanding about this disease.